Colombia : Reforming the Social Safety Net - Rawlings, Laura B. (World Bank, Washington, DC, 2012)
Historically, Colombia's "safety nets" were economic growth and a now unsustainable expansion of social services, notably in health, education, and pensions. Social assistance (SA) was not included in the dramatic social sector reforms of the 1990s, implying that the social safety net did not benefit from increased spending, decentralization and the strategic prioritization afforded to other social sector areas. SA remains under-financed compared to national demands and international norms (Box 1). Furthermore, the SA programs that could have provided a safety net during the crisis were hampered by structural constraints, including poor poverty targeting in certain programs, institutional inflexibility, and unfocused mandates. The Government of Colombia asked the World Bank and Inter-American Development Bank (IDB) to help craft Colombia's social safety net was reviewed and a number of steps taken, including: (i) rapid crafting of a short-term emergency safety net investment program called the Social Support Network (Red de Apoyo Social, RAS); (ii) a poverty assessment and a social safety net assessment; and (iii) implementation of two social sector adjustment operations focused on medium term reforms of the social safety net, health and education systems. The Colombia Social Safety Net Assessment included: (i) a risk and vulnerability assessment based on the analysis of new and existing household survey data as well as a rapid qualitative study and (ii) an institutional analysis of Colombia's new and existing federal social assistance programs. With the Colombia Poverty Assessment, this analytical work provided an empirical basis and a participatory process for outlining priorities for reforming the social protection system.